Effects of drying temperature on the sourness of dehydrated libas (Spondias pinnata) leaves - Damaso, Catherine Hofileña (2010.)
This study was aimed to establish a method aimed at the preservation of the sour libas Spondias pinnata) leaves, in order to promote further utilization and cultivation.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Libas; Spondias pinnata